2020
DOI: 10.1111/bdi.12904
|View full text |Cite
|
Sign up to set email alerts
|

Functioning in euthymic patients with bipolar disorder: A systematic review and meta‐analysis using the Functioning Assessment Short Test

Abstract: Objectives Systematically review the prevalence of functional impairment (FI) in euthymic patients with bipolar disorder (BD), as assessed only with the Functioning Assessment Short Test (FAST), explore the prevalence of this impairment among all the domains, identify the most compromised of them and the clinical variables associated with low functioning in this population. Methods Meta‐analyses were performed, searching for relevant papers published from 2007 to 2019 in Medline, Embase, Cochrane, PsycINFO dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 84 publications
2
22
1
Order By: Relevance
“…Bipolar disorder (BD) is a serious and recurrent mental disease marked by cyclic mood episodes of opposite polarity alternating with intervals of symptomatic remission. As a complex disorder, it is characterized by heterogeneous clinical manifestations and outcomes (Joslyn et al, 2016), which cause substantial damage to the patient's quality of life, social support and functionality (Léda-Rêgo et al, 2020;Studart et al, 2016Studart et al, , 2015. Furthermore, the risk of suicide is elevated in these patients (Dome et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorder (BD) is a serious and recurrent mental disease marked by cyclic mood episodes of opposite polarity alternating with intervals of symptomatic remission. As a complex disorder, it is characterized by heterogeneous clinical manifestations and outcomes (Joslyn et al, 2016), which cause substantial damage to the patient's quality of life, social support and functionality (Léda-Rêgo et al, 2020;Studart et al, 2016Studart et al, , 2015. Furthermore, the risk of suicide is elevated in these patients (Dome et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Our results also corroborate with the present literature, where the subtests (autonomy, occupational functioning, cognitive functioning, and interpersonal relationship), seem to present the greatest impacts. In a recent categorical meta-analysis that included 11 other studies, with a total sample of 1083 patients, the prevalence of global functional impairment was 58.6%.Regarding specific domains, the meta-analysis showed a prevalence of impairment in the following domains: 65.6% in occupational, 49.2% in cognitive, 42.6% in autonomy, 42.1% in interpersonal relationships, 29.2% in leisure, and 28.8% in the field of financial issues -all of them statistically significant [86]. Regarding the FAB test, and confirming one of our initial hypotheses, we observed a similar phenomenon.…”
Section: Discussionmentioning
confidence: 74%
“…They observed that depressive symptomatology together with neurocognitive impairments related to verbal memory and EF are predictor variables of long-term functional outcome in BD.In a recent categorical meta-analysis which included 11 other studies, with a total sample of 1083 patients, the prevalence of global functional impairment was 58.6%. Regarding the specific domains, the meta-analysis presented an impairment prevalence in the following domains: 65.6% in the occupational, 49.2% in the cognitive, 42.6% in the autonomy, 42.1% in the interpersonal relationships, 29.2% in the leisure, and 28.8% in the financial issues domain -all of which were statistically significant [86]. In another study on the relationship between cognitive and occupational function in euthymic patients, it was reported that over six months, cognitive measures at the time of symptomatic recovery, particularly in the domains of working memory/attention and speed of processing, were strongly associated with…”
Section: Discussionmentioning
confidence: 95%